2020
DOI: 10.1021/acsabm.0c00381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lanthanide-Doped Upconverting Nanoparticles for in Vitro and in Vivo Applications

Abstract: Because of their unique physicochemical properties, lanthanide-doped upconverting nanoparticles (Ln-UCNPs) have exceptional potential for biological applications. However, the use in biological systems is hampered by the limited understanding of their bionano interactions. Our multidisciplinary study has generated these insights through in-depth and quantitative analyses. The Ln-UCNPs examined here are spherical, monodisperse, and stable in aqueous environments. We show that Ln-UCNPs were associated with HeLa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…An amphiphilic block copolymer poly(oligo-(ethylene glycol) methyl ether acrylate)-block-poly-(monoacryloxy ethyl phosphate) (POEGA-b-PMAEP), which contained two C-PO-(OR) 2 groups, was used to coat NaGdF 4 / 49% Yb 3+ ,1% Tm 3+ /NaYF 4 UCNPs to form stable and monodispersed nanoparticles. 208 Treatment with UCNPs for 72 h with a concentration of 100 μg mL −1 did not cause any significant changes to the metabolic activities of HeLa (cervical cancer) and LLC-PK1 (renal proximal tubule) cells under irradiation of 980 nm laser (0.918 W/cm 2 ). Furthermore, sublethal effects such as stress responses or other changes in cell physiology were studied by quantifying the impact on the nuclear lamina, nucleoli, and Nrf2 and NF-κB, which are two nuclear transport factors that regulate the oxidative stress response.…”
Section: Toxicity Of Polymer-coated Ucnpsmentioning
confidence: 88%
See 1 more Smart Citation
“…An amphiphilic block copolymer poly(oligo-(ethylene glycol) methyl ether acrylate)-block-poly-(monoacryloxy ethyl phosphate) (POEGA-b-PMAEP), which contained two C-PO-(OR) 2 groups, was used to coat NaGdF 4 / 49% Yb 3+ ,1% Tm 3+ /NaYF 4 UCNPs to form stable and monodispersed nanoparticles. 208 Treatment with UCNPs for 72 h with a concentration of 100 μg mL −1 did not cause any significant changes to the metabolic activities of HeLa (cervical cancer) and LLC-PK1 (renal proximal tubule) cells under irradiation of 980 nm laser (0.918 W/cm 2 ). Furthermore, sublethal effects such as stress responses or other changes in cell physiology were studied by quantifying the impact on the nuclear lamina, nucleoli, and Nrf2 and NF-κB, which are two nuclear transport factors that regulate the oxidative stress response.…”
Section: Toxicity Of Polymer-coated Ucnpsmentioning
confidence: 88%
“…Moreover, the in vivo model organism Caenorhabditis also verified the lack of toxicity of UCNPs. 208 8.4. Toxicity of PAA-Coated UCNPs.…”
Section: Toxicity Of Polymer-coated Ucnpsmentioning
confidence: 99%
“…Dana M. et al tested their NaGdF4:Tm 3+ Yb 3+ nanoparticles on a variety of cancer cell lines and C.elegans. detected no toxicity over a wide concentration range [74]. For the same kind of particle, Huaiyong Xing et al showed after seven days post-injection to the mice, the NaGdF4:Tm 3+ ultra-small nanoparticle could be excreted into feces and urine [75].…”
Section: Biosensing and Other Biomedical Applications Of Lanthanide Nanomaterialsmentioning
confidence: 99%
“… 100 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 In this pipeline, the RE nanoparticles have tremendous potential for bone graft development since it has versatile bio applications, including an antioxidant to antimicrobial effect. 122 , 123 , 124 Furthermore, RE metals can be doped in the abovementioned nanoparticles to redevelop the smart nano‐biomaterials with improved antimicrobial, immunomodulatory potential of ceria, 125 , 126 the osteo‐angiogenic effect of europium, 127 , 128 , 129 contrast imaging potential of Gd, 130 , 131 and laser irradiation property of neodymium. 132 , 133 This review exemplifies the role of various RE nanomaterials for the therapeutic modulation of these important bone cells.…”
Section: Nanomaterials and Cells Involved In Bone Regenerationmentioning
confidence: 99%